Toxicity of combined exposure to acrylamide and Staphylococcus aureus. (2022) - Shimamura, Yuko; Yui, Takuya; Horiike, Hayao; Masuda, Shuichi
Abstract: In the current study, the aim was to examine the toxicity of combined exposure to acrylamide and Staphylococcus aureus . We investigated the effect of staphylococcal enterotoxin A (SEA), a toxin produced by Staphylococcus aureus, on the oxidation induced DNA damaging potency of acrylamide in mouse spleen cells using an Formamidopyrimidine-DNA glycosylase-modified (FPG)-modified comet assay. Parameters like tail moment, tail length, and % tail DNA as indicators of DNA damage were significantly increased in the combined acrylamide and SEA treatment compared with SEA or acrylamide alone. Further, we examined the effects of acrylamide and its epoxide metabolite glycidamide on overall production of SEA, SEA mRNA gene expression, and on the formation of biofilm of S. aureus . Acrylamide significantly increased the SEA expression level and SEA production in S. aureus . Acrylamide also significantly increased biofilm formation in S. aureus without affecting its growth rate. Moreover, the addition of acrylamide significantly increased the expression of S. aureus virulence factors RNAIII and ica A in fetal bovine serum. Our results showed that combined exposure to acrylamide and S. aureus or its toxin enhanced their chemical and biological toxicities. Graphical Abstract: ga1 Highlights: The combined exposure of acrylamide and bacterial toxins enhanced the genotoxicity of AA. Acrylamide enhanced the expression and production of staphylococcal enterotoxin A. Acrylamide enhanced the biofilm formation of S. aureus.